2014
DOI: 10.1159/000367790
|View full text |Cite
|
Sign up to set email alerts
|

Redundant and Cooperative Interactions between TLR5 and NLRC4 in Protective Lung Mucosal Immunity against <b><i>Pseudomonas aeruginosa</i></b>

Abstract: Flagellin is the major structural component of flagella expressed by Pseudomonas aeruginosa (PA) and other bacteria. This protein has been shown to activate the Toll-like receptor TLR5 and the Nod-like receptor Nlrc4/Ipaf, culminating in the expression of innate cytokines and antimicrobial molecules. In this study, we tested the hypothesis that TLR5 and Nlrc4 in combination are required for maximal protective lung innate mucosal immunity against PA. To test this hypothesis, we compared innate immune responses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 48 publications
0
31
1
Order By: Relevance
“…Pattern recognition receptors (PRRs) co-operate to recognize a variety of microbial infections by sensing microbial or danger molecules [4]. The same is true for the diverse NLR-inflammasomes that play redundant and complementary roles, as shown for NLRC4 and TLR-5 [31] and NLRP3 and NLRC4 [43]. Thus, one of the most relevant contributions of the present work derives from the network analysis showing gene interactions and the predicted activation and inhibition of cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Pattern recognition receptors (PRRs) co-operate to recognize a variety of microbial infections by sensing microbial or danger molecules [4]. The same is true for the diverse NLR-inflammasomes that play redundant and complementary roles, as shown for NLRC4 and TLR-5 [31] and NLRP3 and NLRC4 [43]. Thus, one of the most relevant contributions of the present work derives from the network analysis showing gene interactions and the predicted activation and inhibition of cellular functions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have documented the activation of NLRC4 in the presence of type III and type IV secretions involving the injection of needles and formation of pores in host cell membranes causing translocation of virulence factors such as flagellin and rods. These effects are observed in P. aeruginosa, Legionella pneumophila, Burkholderia pseudomallei, and Escherichia coli infections in mice (28,(35)(36)(37)(38)(39). Furthermore, the mechanism of recognition and activation appears to be different for different pathogens.…”
Section: Role Of Inflammasomes In Bacterial Pneumoniamentioning
confidence: 99%
“…Our previous studies showed that mouse corneas pretreated with flagellin, which signals through TLR5, are protective against PA infection (79). Flagellin pretreatment has also been demonstrated to be protective in localized infections of the lung (10, 11) and gut (12), radiation pneumonitis (13), and systematically against biological or physical insults (14). We found that this flagellin-induced protection is due to the reprograming of gene expression in epithelial cells to enhance the innate defense against invasive pathogens.…”
Section: Introductionmentioning
confidence: 99%